2021
DOI: 10.1371/journal.pcbi.1008603
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the structure of the frameshift-stimulatory pseudoknot in SARS-CoV-2 reveals multiple possible conformers

Abstract: The coronavirus causing the COVID-19 pandemic, SARS-CoV-2, uses −1 programmed ribosomal frameshifting (−1 PRF) to control the relative expression of viral proteins. As modulating −1 PRF can inhibit viral replication, the RNA pseudoknot stimulating −1 PRF may be a fruitful target for therapeutics treating COVID-19. We modeled the unusual 3-stem structure of the stimulatory pseudoknot of SARS-CoV-2 computationally, using multiple blind structural prediction tools followed by μs-long molecular dynamics simulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 45 publications
9
73
0
Order By: Relevance
“…The FSE falls within a low z-score region and the base pairs which correspond to these negative values are shown in the model (Figure 1 ). The model of the FSE is largely consistent with recent models ( 68 , 71 ); consisting of two stable hairpins—the first of which contains a loop sequence that forms the proposed pseudoknot ( 13–14 , 72–73 ) by pairing with nucleotides upstream of the second hairpin (Figure 1 ). We also found that this stem was highly conserved, having four base pairs with evidence of covariation.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The FSE falls within a low z-score region and the base pairs which correspond to these negative values are shown in the model (Figure 1 ). The model of the FSE is largely consistent with recent models ( 68 , 71 ); consisting of two stable hairpins—the first of which contains a loop sequence that forms the proposed pseudoknot ( 13–14 , 72–73 ) by pairing with nucleotides upstream of the second hairpin (Figure 1 ). We also found that this stem was highly conserved, having four base pairs with evidence of covariation.…”
Section: Resultssupporting
confidence: 82%
“…cannot predict the pseudoknot directly, however, the generated model does leave the pseudoknot forming nucleotides sufficiently unpaired to allow for the interaction to occur. Comparing the non-pseudoknotted base pairs predicted by to two models built using cryo-EM data (one for ribosome-bound RNA ( 74 ) and one for free RNA ( 14 ), we find that predicts only slightly different helixes from either other model (Figure 1 ). Specifically, the ribosome-bound model did not contain the two closing base pairs of the Stem 1 terminal loop, while both the ribosome-bound and free RNA models did not have the two basal pairs predicted by in Stem 3 (both had G13503 base paired to C13476 to extend Stem 1).…”
Section: Resultsmentioning
confidence: 95%
“…For SARS-CoV FSE, the 3_6 pseudoknot was taken as the consensus structure, 13,19,58 and by extension to SARS-CoV-2, it continues to be the prevailing FSE structure. 15,21,3537 Using various techniques and sequence lengths, 12 out of the 18 papers show a major 3_6 pseudoknot: iterative 2D prediction for 68 nt; 23 3D modeling and MD simulation for 68 nt; 21 NMR spectroscopy complemented with DMS footprinting for 68 nt; 35 2D, 3D, and MD simulation for 77 nt and 84 nt; 22 small-angle X-ray scattering for 85 nt; 15 DMS-MaPseq for 85 nt; 30 homology model for 88 nt; 37 Cryo-EM for 88 nt 29 and 118 nt; 36 deep sequencing for 1475 nt. 38 All except the last two studies use short FSE lengths of 68-88 nt, and most are in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Even using similar methods such as chemical structure probing can lead to different conformations for different sequence lengths. In particular, the 77 nt FSE 5′ end, which was assumed to be an unpaired spacer region, 15,21,36 can form multiple mutually exclusive stems (our 3_3, 3_5 Stem 2, or AS1). The spacer region length is considered to have a critical impact on frameshifting efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…This way the factor modulates RNA folding pathways and thus plasticity, which is a common feature of RNA-based regulation of biological processes 59,60 . In fact, structural plasticity has been reported as a hallmark of -1PRF stimulatory RNAs 47 . Our single-molecule pulling experiments indicate that ZAP-S binds to the SARS-CoV-2 -1PRF RNA directly and interferes with the refolding of the stimulatory RNA structure in vitro.…”
Section: Discussionmentioning
confidence: 99%